Oxygen pressure-mediated cation stoichiometry, microstructure, and properties of epitaxial perovskite thin films - Li, Zhipeng (2013)
Transition metal oxides, especially those with perovskite structure, have attracted great attention due to their rich and useful physical properties, such as high temperature superconductivity, ferroelectricity and ferromagnetism. Functional perovskite films have profited greatly from the steady advances in thin film growth technologies, which allow nanoscale engineering in order to fabricate oxide electronics devices. Within the family of perovskite, La1-xSrxMnO3 (0.2 < x < 0.5) compounds are viewed as one of key building blocks of oxide spintronic devices due to their desirable properties, such as colossal magnetoresistance (CMR) and half metallicity. When they are used as electrodes in combination with ferroelectric barrier layers, highly spin-polarized multiferroic tunnel junctions can be formed. However, cation off-stoichiometry at the epitaxial interfaces between manganites and other materials can lead to interfacial dead layers, severely reducing the performances of the tunnel junction devices. In this work, transmission electron microscopy (TEM) and synchrotron-based spectroscopies were used to demonstrate that oxygen vacancies serve as a critical factor for modifying the cation stoichiometry in pulsed laser deposited La0.8Sr0.2MnO3 films. Near the manganite/SrTiO3 interface, A-site cations (La/Sr) are in excess when oxygen vacancies are induced during the film growth, partially substituting Mn cations. Simultaneously, Sr cations migrate towards the film surface and form a SrO rock-salt monolayer. Consequently, a gradient of the Mn nominal valence, varying from +3.6 to +3.2, is observed along the film growth direction through quantitative analysis of electron energy loss spectra, leading to anomalous magnetic properties. The results narrow the selection range of useful oxygen pressures during deposition, and demonstrate that accurate interface and surface cation stoichiometry can only be achieved after oxygen vacancies are eliminated in films during growth. This finding suggests that oxygen pressure serves as a tuning parameter for the interfacial dead layers and, hence for control over device performance. In addition, we studied growth, microstructure and properties of perovskite superlattices composed of ferromagnetic La0.8Sr0.2MnO3 and ferroelectric BaTiO3. Increasing demand for spintronic devices, such as high-density memory elements, has generated interest in magnetoelectric coupling and multiferroic materials. The manipulation of electron spin by ferroelectric polarization or vice versa, can generate an additional degree of freedom besides electric and magnetic ordering, leading to the possibility of four-state memories. In artificial heterostructures, magnetoelectric coupling occurs only near the interfacial area. Due to the high interfacial area to volume ratio, multiferroic multilayer/superlattice is viewed as one of the most efficient ways to enhance the magnetoelectric coupling coefficient. However, both ferroelectric and ferromagnetic properties are difficult to be maintained when materials are shrunk to ultrathin layers. Interface dipoles and spin modulations are thought to create dead layers in ferroelectricity and ferromagnetism, respectively. Whether these dead layers are intrinsic has so far been controversial. In this work, we demonstrated that the degradation of multiferroic properties in the La0.8Sr0.2MnO3/BaTiO3 superlattices is strongly correlated to the local strain fields and cation nonstoichiometry induced by cation defects. This conclusion was arrived by combining the atomic-scale electron microscopy, piezoelectric force microscopy and low-temperature magnetism measurements. When the defects, such as pure edge dislocations and planar defects, were eliminated by increasing oxygen pressure during the film growth, both robust ferroelectricity and ferromagnetism were observed. Therefore, we conclude that the presence of cation defects has been the major obstacle limiting the functionalities of multiferroic superlattices with ultrathin ferroic layers and high oxygen pressure is required to deposit films with nearly bulk ferroic properties. In summary, this work offers a well-documented insight into another critical growth parameter (besides the well-studied laser fluence effect) that can result in off-stoichiometric pulsed laser deposited La0.8Sr0.2MnO3 thin films and La0.8Sr0.2MnO3/BaTiO3 multiferroic superlattices. Controlling the oxygen pressure during growth is crucial to achieving better interfaces, surfaces and microstructures, paving the way for fabrication of complex oxide devices with high performances.